Proteolysis and the domain organization of myosin subfragment 1. - Mornet, D (1984)
Because the proteolytic cleavage of a folded polypeptide depends not only on the specificity of the protease but on the nature of the folding, we investigated the cleavage of (chymotryptically produced) subfragment 1 (designated "S-1") or "head" segment of myosin by seven proteases with different specificities. All seven produced approximately the same three fragments of S-1--namely, fragments (from the NH2 terminus) of 27, 50, and 20 kilodaltons, suggesting that in intact S-1 these fragments are distinct domains. The same proteases were used to hydrolyze the MgADP complex of S-1. All failed to do so except trypsin, which, as found earlier [Hozumi, T. (1983) Biochemistry 22, 799-804], makes two additional cleavages. This result suggests that the conformational change induced by MgADP opens up only a small stretch of polypeptide chain, which stretch happens to be vulnerable to trypsin.